2020
DOI: 10.1108/jmlc-05-2020-0058
|View full text |Cite
|
Sign up to set email alerts
|

Crime control in Nigeria: how relevant is remittance inflow?

Abstract: Purpose This paper aims to draw on extant literature to ascertain the relevance of remittance receipts in improving the level of crime control in Nigeria. Design/methodology/approach The study uses time series data spanning for a period of 1986–2017. It adopts dynamic ordinary least square (DOLS), vector auto regression impulse response function, variance decomposition and Toda and Yamamoto causality approach to analyse the data. Findings The following findings are established: DOLS shows that remittance r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 24 publications
0
3
1
Order By: Relevance
“…Second, we find that there is bidirectional causality between remittances and homicides in the short run. Out findings are different from those of Brito et al (2014), Ajide (2021) and others. They found that remittances are likely to reduce crime rates.…”
Section: Discussion Policy Implications and Concluding Remarkscontrasting
confidence: 98%
See 3 more Smart Citations
“…Second, we find that there is bidirectional causality between remittances and homicides in the short run. Out findings are different from those of Brito et al (2014), Ajide (2021) and others. They found that remittances are likely to reduce crime rates.…”
Section: Discussion Policy Implications and Concluding Remarkscontrasting
confidence: 98%
“…It would be important to control for these variables so that one can tease out statistically the relationship between remittances and homicides that is not confounded by other influences. For practical and data availability considerations, we have to settle on three control variables that have been used in the literature (Brito et al , 2014; Coon, 2015; Mahesh, 2020; and Ajide, 2021). These variables are GDPPC, UR and consumer price index (CPI).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The strategy of the Dubai Police is based on preventing and reducing crime by implementing several crime-fighting initiatives that harness the power of artificial intelligence and advanced technology to bolster public safety and security. These initiatives encompass diverse programs, such as Dubai Police's Smart Homes Transformation Plan 2018-2021(Dubai Police, Open Data 2023, which aimed to entirely convert residences in the Emirate of Dubai into smart homes, enabling homeowners to monitor their homes remotely with a 100% success rate. The International Crime-Fighting Program is designed to adopt a professional approach to tracking criminal activities worldwide, strengthening partnerships in crime detection, and apprehending international criminal organizations.…”
Section: Introductionmentioning
confidence: 99%